Preparação, caracterização e aplicação de nanofolhas de nitreto de boro hexagonal - Sara Machado Queiroz (2021)
Two-dimensional materials have become a topic of great interest in recent years due to their promising properties and application possibilities. Since the first-time graphene was obtained, more and more two-dimensional materials became an object of research among the scientific community. Among the two-dimensional materials that received great prominence on the scientific community, the hexagonal boron nitride nanosheets (h-BNNS) can be mentioned. Hexagonal Boron Nitride (h-BN) is a compound with Nitrogen (N) and Boron (B) atoms alternated in a hexagonal arrangement in the basal plane. The B and N atoms are alternately stacked directly on top of each other in adjacent atomic layers. H-BN is nearly transparent, with important optical properties, electrically insulating, thermally and chemically stable, and exhibits good oxidation resistance at high temperatures (up to ~800°C). According to the chosen route, h-BN can be obtained as nanosheets, nanotubes, nanoribbons, and others. In particular, h-BNNS exhibit mechanical and thermal properties similar to their isoelectronic counterpart, the graphene. However, the bonds between B and N take on a partially ionic character throughout the sheet due to their different electronegativity, resulting in specific properties of h-BNNS. Thanks to their complementary properties to graphene oxide (GO), such as being electrical insulator and having thermal and chemical stability, especially in oxidizing environments, h-BNNS can be used to build hybrids with GO with controllable electrical conductivity and greater resistance to degradation at high temperatures for the obtained compound and thus increasing its application possibilities. Another possibility is the functionalization or passivation of h-BNNS by different chemical species. Among the groups used to functionalize h-BN, hydroxyl groups bring great interest once they result in properties to material such as great stability, good dispersibility in water and in other solvents, allowing its incorporation in matrices and leading to good application perspectives. Moreover, it is expected that the introduction of these functional groups is sufficient to overcome van der Waals forces and interactions between adjacent h-BN layers, resulting in its exfoliation. In the present work, functionalized (h-BN-OH) and exfoliated (h-BNNS-OH) h-BN was prepared by methods already reported in the literature and by different associations of these. Three functionalization methods were used to obtain h-BN-OH: a) reflux for 24 hours in NaOH(aq), b) chemical treatment under heating in autoclave in NaOH(aq) medium for 2 hours at 180°C, varying the h-BN x NaOH ratio, c) ball milling in NaOH(aq) medium, varying the milling time, number and size of balls, and d) combination of methods b and c. After obtaining h-BN-OH by the described methods, the material with the highest colloidal stability result was exfoliated. Exfoliation of h-BN-OH was performed by top-down methods, namely: a) liquid exfoliation in 25% V V-1 isopropyl alcohol aqueous solution (IPA(aq)) by sonication, b) adapted high-energy ball milling in basic medium (NaOH(aq) at 2 mol L-1) and c) combination of these methods, aiming to promote a more stable dispersion of h-BNNS-OH in IPA(aq). The optimized route to obtain h-BNNS-OH was then determined. In order to determine the optimum process condition, the material obtained was characterized regarding the quality, morphology and topography of the sheets, stability of the dispersions, degree of functionalization and chemical and structural characteristics. As a result, nanosheets were obtained with approximately 10 to 30 nm thick and with a functionalization degree of less than 1%. The dispersions in IPA(aq) showed high macroscopic stability and excellent colloidal behavior over time. h-BNNS in the range of 25 and 34 layers were obtained, with a yield of 36,7%, a good balance between technical requirements through a practical process. Using the best obtained h-BNNS-OH sample, hybrids with GO were prepared by two different processes and the material was evaluated for thermal stability and morphology. A maximum degradation rate temperature gain of 35°C relative to GO was observed.